Atuação bibliotecária em hospitais de ensino: um panorama da Região Centro-Oeste do Brasil - Mendes, Neide Trindade (Universidade Federal de São Carlos, 2023)
The insertion of the librarian in the health context is increasingly necessary, not only to train users who are experts in health regarding the sources to be consulted, but in the guidance and delivery of reliable information, filtering, treating and also certifying the veracity of information that will be disseminated to end users. In this sense, the question arises what is the professional profile and working conditions of librarians who work in teaching hospitals in the Central-West region of Brazil? Therefore, we seek to present an overview of the professional profile and respective working conditions of clinical librarians working in teaching hospitals in the Central-West region of Brazil. This is an exploratory and descriptive study. As methodological procedures, bibliographical surveys were carried out using the bases of the Information Science Database (BRAPCI), Brazilian Digital Library of Theses and Dissertations (BDTD), Scientific Electronic Library Online (SciELO – Brazil), ENANCIB Annals and Portal de Capes periodicals. To collect data, we used a semi-structured questionnaire that was prepared via Google Forms, with a total of 20 questions, all anonymous and freely chosen in order to avoid bias in the answers. The results demonstrate that the majority of the 11 respondents identify themselves as information librarians and that the main difficulties in this niche of professional activity are related to the difficulty in understanding technical language; use appropriate information technology to organize and disseminate information; assess information needs in order to meet identified needs; master the sources of information in the area; carry out specializations and/or training; develop and manage information services and; provide support and training for users of the library or information service. In conclusion, the work of health librarians in the Central-West region is still incipient, and it is opportune to increase the supply of courses and specific training that trains librarian professionals who wish to work in the health context and in clinical environments.
Librarian work in teaching hospitals: an overview of the Central-West Region of Brazil
Keywords: Bibliotecário clínico; Atuação profissional; Hospitais escola; Região centro-oeste; Brasil; Clinical librarian; Professional performance; School hospital; Midwest region; Brazil; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA